How to train your dragon. - Cowell, Criselda (New York : Little Brown and Company, 2003)
Chronicles the adventures and misadventures of Hiccup Horrendous Haddock the Third as he tries to pass the important initiation test of the Viking clan, the tribe of the Hairy Hooligans, by catching ang training a dragon.
Keywords: Vikings- -- juvenile fiction; Dragons- -- fiction; Vikings- -- fiction; Humorous stories